Islamic Spirituality in Medical Doctor Curriculum Development: A Framework for Integration of Naqlī and ʿAqlī Knowledge - Nur Izah Ab Razak; Yusoff Sharizal Yusoff Azmi Merican; Wan Noraini Wan Sulaiman; Nurul Asyiqin Yusof (Universiti Sains Islam Malaysia, 2026)
Maʿālim Al-Qurʾān Wa Al-Sunnah, Volume 21 Issue 2 Page (331–358)